MANAGEMENT OF CONSTRUCTION OBJECTS WITHIN THE SYSTEMATIZATION OF RESIDENTIAL REAL ESTATE PROPERTIES - Diyarova Mahliyo Islamovna (Journal of Artificial Intelligence and Digital Economy, 2024)
This article considers residential real estate, built by construction enterprises, as an effective investment object and a reliable source of income under conditions of innovative development. The methods of effective management of construction objects within the systematization of the specific properties of residential real estate are extensively discussed